Medical Students' Empathy for Vulnerable Groups: Results From a Survey and Reflective Writing Assignment. (December 2017) - Wellbery, Caroline; Saunders, Pamela A.; Kureshi, Sarah; Visconti, Adam
Abstract : Purpose: As medical education curricula increasingly acknowledge the contributions of the social determinants of health to individual health, new methods of engaging students in the care of vulnerable groups are needed. Empathy is one way to connect students with patients, but little is known about how to nurture students' empathy on behalf of populations. This study examined the relationship between individual and social empathy as groundwork for cultivating students' empathy for vulnerable groups. Method: In 2014–2015, first-year medical students completed the Social Empathy Index at the start and end of a two-semester population health course, and they completed a reflective writing assignment exploring the challenges of caring for vulnerable patients. Pre- and posttest mean survey scores were compared, and reflective writing assignments were analyzed for themes concerning social empathy. Results: Data from 130 students were analyzed. Scores for the contextual understanding of systemic barriers domain increased significantly. There was a trend toward increased cumulative social empathy scores that did not reach statistical significance. Students' essays revealed three themes relating to individual empathy as the foundation for social empathy; civic and moral obligations; and the role of institutional practices in caring for vulnerable groups. Conclusions: This study extends understanding of empathy beyond care for the individual to include care for vulnerable groups. Thus, social empathy may function as a valuable concept in developing curricula to support students' commitment to care for the underserved. Educators first need to address the many barriers students cited that impede both individual and social empathy. Abstract : Supplemental Digital Content is available in the text.